High‐Temperature Reduction of Calcium Alginate to Carbon Sphere for Efficient Removal of Bivalent Cadmium. Issue 31 (16th August 2019) - Cheng, Yalin; Wang, Kaiqian; Tu, Biyang; Xia, Yang; Zhang, Jiaqian; Xue, Shan; Tao, Haisheng
Abstract: A carbon sphere was synthesized by high temperature reduction using alginate as a carbon source. The material was characterized by Fourier transform infrared spectrometer, X‐ray diffraction, scanning electron microscopy and energy dispersive analysis. The carbon sphere is reticulated and porous at the microscopic level. For Cd(II) removal experiments, the results showed that the carbon sphere had an excellent effect for the remove of Cd(II), and the adsorption obeyed pseudo‐second‐order kinetic model and the Langmuir adsorption isotherm model. The adsorption capacities of Langmuir isotherm were 149, 167, 196 mg⋅g −1 at 288 K, 298 K and 308 K, respectively. In general, the carbon sphere has a good application prospect for treating cadmium‐containing wastewater. Abstract : Calcining calcium alginate gel into carbon sphere at one step through high‐temperature reduction, influence of the dosage, pH, reaction time, concentration and temperature have been studied, and the adsorption mechanism of the material was preliminarily analyzed through the adsorption kinetic and thermodynamic models.